Designing and Evaluating a Testbed for the Matter Protocol: Insights into User Experience - AlRabah, Abdulrahman (2024)
—As the integration of smart devices into our daily environment accelerates, the vision of a fully integrated smart home is becoming more achievable through standards such as the Matter protocol. In response, this research paper explores the use of Matter in addressing the heterogeneity and interoperability problems of smart homes. We built a testbed and introduce a network utility device, designed to sniff network traffic and provide a wireless access point within IoT networks. This paper also presents the experience of students using the testbed in an academic scenario.